Pengaruh kreativitas iklan, kualitas pesan iklan, dan daya tarik iklan terhadap sikap pada merek melalui efektivitas iklan pada iklan merek â€œXâ€ di Surabaya - Widowati, Theresia Intan (Kajian Ilmiah Mahasiswa Manajemen, 2015)
In the midst of intense competition in the business world, companies are required to have a competitive advantage in order to compete with other companies in the global business. One of the many ways that companies can do to attract customers is through advertising. The sole purpose of advertising is to introduce a product or service to consumers resulting in increasing of awareness and then to influence or change the attitudes of consumers to a change in behavior as a company want. The challenge is in the how to design an ad that is unique, creative, and attractive so that it could be effective. In this case, a brand named â€œXâ€ is no exception in doing a good advertising campaign using television and print media. This study will analyze the influence of advertising creativity, quality advertising messages, and advertising attractiveness against brand attitudes through advertising effectiveness. This study will be using SEM (Structural Equation Modeling) analysis by AMOS software. The selected population is the people of Surabaya with criteria aged over 18 years old, watched or seen brand â€œXâ€â€™s commercial series, and is a consumer of the â€œXâ€ products. The samples picked are 120 respondents by using convenience sampling method. The results showed that while advertising creativity is not proven significant to advertising effectiveness, the quality advertising messages and advertising attractiveness do significantly influence the advertising effectiveness. The advertising effectiveness is also shown to have a significant influence to the brand attitudes.